Local Health Departments' Engagement in Activities to Address Opioid Use and Abuse: The Influence of Surveillance Systems' Use. Issue 4 (July 2021) - Nguyen, Tran Ha; Shah, Gulzar H.; Khurshid, Anjum; Olivas, Maria I.
Abstract : Aims: To examine the extent to which local health departments (LHDs) conduct activities to address opioid use and abuse. To test the hypothesis that (i) LHDs' access to data from an electronic syndromic surveillance system is associated with conducting activities to address opioid use and abuse, and (ii) among those LHDs with access to syndromic surveillance data, the use of syndromic and other surveillance data on opioid-related events is associated with LHDs' report of conducting activities to address opioid use and abuse. Methods: Logistic regression was used to analyze data from the 2018 Forces of Change Survey of a statistically representative sample of 966 LHDs, of which 591 participated in the survey. Results: The LHDs' access to a syndromic surveillance system was significantly associated with their report of conducting activities to address opioid use and abuse. Compared with LHDs that had no surveillance systems, odds of participating in activities to address the opioid use or abuse were higher for LHDs that managed their own surveillance systems (adjusted odds ratio, AOR = 3.022, P = .03) and those who had but did not manage their own surveillance systems (AOR = 1.920, P < .01). The LHDs' use of syndromic surveillance systems (AOR = 2.98, P = .01) or other surveillance systems (AOR = 2.21, P = .03) was also associated with higher odds to participate in activities to address the opioid use or abuse (vs no such use). Conclusion: The LHDs are strategically well positioned to play their role in addressing this multifaceted epidemic. Access to data or information from electronic syndromic surveillance systems that use hospital emergency department data might significantly improve LHDs' engagement in conducting activities to address opioid use and abuse within their communities while building their capacity to face the next epidemic.